2021
DOI: 10.1002/biot.202100189
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme‐processed guide RNA enhances virus‐mediated plant genome editing

Abstract: In virus-induced gene-editing system, subgenomic promoters have been used to express guide RNAs (gRNAs). However, the transcription initiation site of the subgenomic promoters remains elusive. Here, we examined the sequence of gRNAs expressed by subgenomic promoters and found the variable length of overhangs at 5′-end of gRNAs. The overhangs at 5′-end of gRNA decrease the cleavage activity of SpCas9. To overcome this problem, we inserted hammerhead ribozyme between the subgenomic promoter and gRNA and confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…S1 ). Although the mutation was observed in the infected leaves (19.7% ± 2.7%, Oh et al, 2021b ), we found no gene-edited seeds in the pooled M 1 seedlings of TRV2:gPDS-infected 35S:Cas9 ( Supplementary Fig. S1 , Oh et al, 2021b ).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…S1 ). Although the mutation was observed in the infected leaves (19.7% ± 2.7%, Oh et al, 2021b ), we found no gene-edited seeds in the pooled M 1 seedlings of TRV2:gPDS-infected 35S:Cas9 ( Supplementary Fig. S1 , Oh et al, 2021b ).…”
Section: Resultsmentioning
confidence: 67%
“…To develop a VIGE system for N. attenuata , we first generated transgenic N. attenuata expressing SpCas9 under the control of the 35S promoter (35S:Cas9) ( Oh et al, 2021b ). A gRNA was designed to target the N. attenuata phytoene desaturase ( NaPDS ) gene and cloned into the TRV2 vector under the subgenomic promoter of the pea early-browning virus (TRV2:gPDS) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the cargo could be a self-amplifying RNA (saRNA) vector [37]. An saRNA vector could enable the use of a CRISPR base editor, wherein a subgenomic promoter effectively replicates an sgRNA module but weakly replicates the proteinaceous component of the base editor [38,39]. As larger RNA molecules were packaged less efficiently in COURIER, but dual delivery was possible, a trans-amplifying RNA (taRNA) vector could be employed [40].…”
Section: Neuronal Gene Editingmentioning
confidence: 99%
“…Ribozyme‐processed gRNAs are especially favorable to increase mutation frequency. [ 1 ] Trait‐improved cattle were generated through the genome‐editing technology CRISPR–Cas9, by targeting the Myostatin (MSTN) locus which led to offspring with a double‐muscling phenotype. [ 2 ] Chen and coworkers provided perspective on using CRISPR‐based platforms for rapid diagnostics, which could potentially revolutionize and expand our tool kits for tackling future pandemics.…”
mentioning
confidence: 99%